2020
DOI: 10.5194/hess-2020-312
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the role of hydrological pathways in modulating North Atlantic Oscillation (NAO) teleconnection periodicities from UK rainfall to streamflow

Abstract: Abstract. An understanding of multi-annual behaviour in streamflow allows for better estimation of the risks associated with hydrological extremes. This is can enable improved preparedness for streamflow-dependant services such as freshwater ecology, drinking water supply and agriculture. Recently, efforts have focused on detecting relationships between long-term hydrological behaviour and oscillatory climate systems (such as the NAO). For instance, the approximate 7-year periodicity of the NAO has been detect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Although it should be noted that NAOI-rainfall correlations can be sensitive to the method of NAOI calculation, notably the choice between indices derived from station-measured or modelled SLP data [14]. Additionally, studies have explored how these NAO-rainfall deviations variably propagate through catchments to influence streamflow [6,[15][16][17], groundwater [18,19] and fluvial water temperatures [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although it should be noted that NAOI-rainfall correlations can be sensitive to the method of NAOI calculation, notably the choice between indices derived from station-measured or modelled SLP data [14]. Additionally, studies have explored how these NAO-rainfall deviations variably propagate through catchments to influence streamflow [6,[15][16][17], groundwater [18,19] and fluvial water temperatures [20].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the relationship between the NAO Index (NAOI) and recorded hydrological variables in Europe, including river flow (Burt & Howden, 2013), groundwater (Lavers et al, 2015), and seasonal rainfall (West et al, 2019), or calculated water resource variables such as the standardized precipitation index (Moreira et al, 2016). Furthermore, a growing number of studies have detected multi-annual periodicities in hydrological variables river flow and rainfall (Rust et al, 2020), and groundwater level (Neves et al, 2019) that align with weak periodicities detected in the NAOI (Hurrell & Loon, 1997), suggesting that multi-annual cycles in the NAO may affect the occurrence of floods and droughts in Western Europe.…”
mentioning
confidence: 99%
“…Furthermore, Liesch and Wunsch (2019) found significant coherence between NAOI and groundwater level at approximately 6-to 16-year periodicities across the UK, Germany, Netherlands and Denmark. Rust et al (2019;2021a) identified a similar significant 6-to 9-year cycle across a large dataset of groundwater level (59 boreholes) and streamflow (705 gauges) in the UK, which was associated with the principal periodicity of the NAO (of a similar length (Hurrell et al, 2003;Zhang et al, 2011)).…”
Section: Introductionmentioning
confidence: 82%
“…al, 2019; Uvo et al, 2021), than at an annual scale. This is particularly apparent where longer hydrological response times predominate (Rust et al 2021a). For instance, Neves et al (2019) identified significant relationships between the NAOI and groundwater level in Portuguese aquifers and at approximately 6-and 10-year periodicities, with associations to episodes of recorded groundwater drought.…”
Section: Introductionmentioning
confidence: 96%